Low-hygroscopicity medium-temperature curing single-component epoxy adhesive suitable for bonding special-shaped structure composite material and preparation method of low-hygroscopicity medium-temperature curing single-component epoxy adhesive
By adjusting the composition of the epoxy resin and adding specific components, a low-hygroscopic medium-temperature cured single-component epoxy adhesive was prepared, which solved the problem of insufficient fluidity and moisture resistance of existing adhesives, improved the bonding strength and moisture-heat resistance, and met the bonding needs of complex structures.
Patent Information
- Application Number
- CN202411713792.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
The existing single-component epoxy adhesives in dicyandiamide systems are insufficient in fluid resistance and moisture resistance in bonding of special-shaped composite structures, making it difficult to meet the bonding needs of complex structures.
By adjusting the composition of the epoxy resin, a bisphenol A type epoxy resin, a multifunctional epoxy resin, a core-shell toughened epoxy resin, a polysulfur rubber modified resin and a gas-phase white carbon black are introduced, and a low-hygroscopic medium-temperature cured single-component epoxy adhesive is prepared.
It improves the moisture resistance and bonding strength of the adhesive, ensures the stability and durability of bonding in high temperature and high humidity environments, and meets the bonding needs of special-shaped composite structures.
Smart Images

Figure CN119529728A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an epoxy adhesive and a preparation method thereof. Background Art
[0002] As the demand for energy conservation, emission reduction and environmental protection becomes increasingly urgent, more and more research is being conducted on lightweight design. Air transport and new energy vehicles have begun to adopt some resin-based carbon fiber composite materials. Such composite materials have excellent mechanical properties, relatively simple manufacturing processes, and outstanding weight reduction effects compared to metal materials. For the connection between composite materials, welding processes like metal are no longer applicable, and the riveting method will increase the stress at the connection point and easily damage the composite material. Adhesive bonding is one of the main connection methods for composite structures. It is to place adhesive materials between two bonded parts to produce usable connection strength between the bonded objects. Compared with mechanical connection, its main advantages are: no stress concentration caused by drilling, high connection efficiency; good fatigue resistance, sealing and shock absorption performance; can obtain a smooth aerodynamic shape; no galvanic corrosion problems when connecting different materials.
[0003] For bonding some complex carbon fiber composite materials, there are many bonding surface forms such as vertical surface, curved surface, irregular surface, etc., so the requirements for the adhesive's operating period, flowability and other process performance are stringent. Only adhesives with long application period and low flowability can meet the bonding requirements of special-shaped complex structure composites.
[0004] In addition, the moisture resistance of the adhesive is crucial to the bonding strength and durability of such structures. First, during the construction process, due to the complexity of the bonding structure and the long adhesive coating process, the coated adhesive is exposed to the air for a long time, which requires the adhesive to have good resistance to moisture in the air. Second, the composite structure after bonding may be in an environment of high temperature and high humidity for a long time, which requires the adhesive to have good moisture and heat resistance after bonding. Otherwise, long-term moisture and heat aging will lead to bonding failure and cracking at the bonding joints, seriously affecting the overall structure.
[0005] Dicyandiamide epoxy adhesive system is widely used as a one-component epoxy adhesive due to its excellent latency, bonding performance, bulk mechanical properties, etc. As a mature latent epoxy resin curing agent, dicyandiamide can adjust the curing temperature of the adhesive by combining with different accelerators. However, due to the poor solubility of dicyandiamide in epoxy and the presence of more polar groups in the cured product, the moisture and heat resistance of this type of adhesive is relatively poor. Summary of the invention
[0006] The purpose of the present invention is to solve the problem of poor anti-flowability and moisture resistance of medium-temperature curing dicyandiamide system one-component epoxy adhesive for bonding special-shaped composite structures, and to provide a low hygroscopic medium-temperature curing one-component epoxy adhesive suitable for bonding special-shaped structural composites and a preparation method thereof.
[0007] A low-hygroscopic medium-temperature curing one-component epoxy adhesive suitable for bonding special-shaped structural composite materials is prepared by 70 to 90 parts by mass of bisphenol A epoxy resin, 10 to 30 parts by mass of multifunctional epoxy resin, 10 to 30 parts by mass of core-shell toughened epoxy resin, 10 to 20 parts by mass of polysulfide rubber modified resin, 8 to 12 parts by mass of dicyandiamide, 1 to 2 parts by mass of 2-ethyl-4-methylimidazole and 7 to 9 parts by mass of fumed silica.
[0008] A method for preparing a low-hygroscopic medium-temperature curing one-component epoxy adhesive suitable for bonding special-shaped structural composite materials, characterized in that the preparation method is specifically completed according to the following steps:
[0009] 1. Weighing materials:
[0010] Weigh 70 to 90 parts of bisphenol A epoxy resin, 10 to 30 parts of multifunctional epoxy resin, 10 to 30 parts of core-shell toughened epoxy resin, 10 to 20 parts of polysulfide rubber modified resin, 8 to 12 parts of dicyandiamide, 1 to 2 parts of 2-ethyl-4-methylimidazole and 7 to 9 parts of fumed silica by weight;
[0011] 2. Mixing:
[0012] 70 to 90 parts of bisphenol A epoxy resin, 10 to 30 parts of multifunctional epoxy resin, 10 to 30 parts of core-shell toughened epoxy resin, 10 to 20 parts of polysulfide rubber modified resin, 8 to 12 parts of dicyandiamide, 1 to 2 parts of 2-ethyl-4-methylimidazole and 7 to 9 parts of fumed silica weighed in step 1 are added to a reactor, stirred and mixed to obtain a mixture;
[0013] 3. Grinding:
[0014] Grinding the mixture obtained in step 2 using a three-roll mill to obtain a single-component paste adhesive;
[0015] 4. Degassing:
[0016] The one-component paste adhesive obtained in step 3 is mixed for a period of time using a planetary mixer to obtain a low-hygroscopic medium-temperature curing one-component epoxy adhesive suitable for bonding special-shaped structural composite materials.
[0017] Principle of the present invention:
[0018] In order to improve the moisture resistance of the medium-temperature curing dicyandiamide epoxy adhesive, the present invention starts with the curing system, uses dicyandiamide as a curing agent, and uses 2-ethyl-4-methylimidazole as an accelerator. First, the curing reaction degree of dicyandiamide and epoxy resin is promoted by the accelerator; second, a flexible toughening agent containing a water-resistant group is introduced into the epoxy resin structure, which not only improves the moisture resistance of the adhesive, but also increases the bonding strength; third, a multifunctional epoxy resin is introduced to increase the crosslinking density of the adhesive system after curing, thereby improving the moisture resistance of the adhesive. Through multi-faceted synergistic effects, the moisture resistance of the epoxy resin adhesive is improved.
[0019] Advantages of the present invention:
[0020] 1. The low hygroscopic medium temperature curing one-component epoxy adhesive prepared by the present invention for bonding special-shaped structural composites has a curing condition of 120°C / 90min. The flow distance is less than 3mm; the glass transition temperature is (128-130)°C, the shear strength of the bonded carbon fiber / bismaleimide composite material at room temperature is (31.2-33.7)MPa, and the shear strength at 80°C is (28.4-30.9)MPa;
[0021] Second, the adhesive is first applied to the bonded surface, and then exposed to the environment of 25℃±2℃, 60%RH humidity for 24 hours, and then laminated, bonded, and pressurized for curing. The shear strength of the bonded carbon fiber / bismaleimide composite material at room temperature is (32.1~34.5)MPa, and the shear strength at 80℃ is (28.6~30.8)MPa;
[0022] 3. After boiling in boiling water for 7 days, the glass transition temperature is (80-82)℃ / (119-121)℃, the shear strength of the bonded carbon fiber bismaleimide composite material at room temperature is (30.2-32.9)MPa, the shear strength at 80℃ is (14.5-16.4)MPa, and the water absorption rate is (5.9-6.2)%;
[0023] Fourth, the polysulfide rubber modified resin in the present invention has a good toughening effect in the epoxy resin adhesive. After addition, the shear strength of the epoxy adhesive can be improved, and the moisture resistance of the medium-temperature curing dicyandiamide system one-component epoxy adhesive is significantly improved, solving the problem of a large decrease in the bonding shear strength of the medium-temperature curing dicyandiamide system one-component epoxy adhesive after high temperature and high humidity.
[0024] The invention can obtain a low-hygroscopicity medium-temperature curing single-component epoxy adhesive suitable for bonding special-shaped structural composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The graph is a water absorption rate diagram of the adhesive prepared by adding polysulfide rubber modified resin in Example 1 and the adhesive prepared by not adding polysulfide rubber modified resin in Comparative Example 1 after being immersed in boiling water;
[0026] Figure 2 The initial DMA graphs are of the adhesive prepared by adding polysulfide rubber modified resin in Example 1 and the adhesive prepared by not adding polysulfide rubber modified resin in Comparative Example 1;
[0027] Figure 3 DMA graphs of the adhesive prepared by adding polysulfide rubber modified resin in Example 1 and the adhesive prepared by not adding polysulfide rubber modified resin in Comparative Example 1 after being immersed in boiling water for 7 days. DETAILED DESCRIPTION
[0028] Specific implementation method 1: The epoxy adhesive described in this implementation method is made of 70 to 90 parts of bisphenol A epoxy resin, 10 to 30 parts of multifunctional epoxy resin, 10 to 30 parts of core-shell toughened epoxy resin, 10 to 20 parts of polysulfide rubber modified resin, 8 to 12 parts of dicyandiamide, 1 to 2 parts of 2-ethyl-4-methylimidazole and 7 to 9 parts of fumed silica in parts by mass.
[0029] Specific implementation method 2: This implementation method is different from the specific implementation method 1 in that the bisphenol A epoxy resin is E51 or E54. The other steps are the same as those of the specific implementation method 1.
[0030] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that the multifunctional epoxy resin is triglycidyl p-aminophenol or triglycidyl m-aminophenol. The other steps are the same as those of specific embodiment 1 or 2.
[0031] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the core-shell toughened epoxy resin is MX-125, MX-153, MX-154 or MX-257, all of which are purchased from Kanebuchi Co., Ltd. of Japan. The other steps are the same as those of specific embodiments 1 to 3.
[0032] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the fumed silica is TS-530, TS-610 or TS-720. The other steps are the same as those of specific embodiments 1 to 4.
[0033] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that: the preparation method of the polysulfide rubber modified resin is specifically completed according to the following steps:
[0034] 100g of low-viscosity epoxy resin and 10g to 100g of liquid polysulfide rubber are added to the reactor, and the temperature is raised from room temperature to 120°C to 130°C at a heating rate of 1°C / min to 5°C / min under a stirring speed of 300r / min to 500r / min, and the mixture is continuously stirred at 120°C to 130°C for 4h to 5h to obtain a polysulfide rubber modified resin. The other steps are the same as those of the first to fifth embodiments.
[0035] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the low-viscosity epoxy resin is 1,2-cyclohexanediol diglycidyl ether or 1,4-cyclohexanedimethanol diglycidyl ether. The other steps are the same as those of specific embodiments 1 to 6.
[0036] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that the liquid polysulfide rubber is JLY-121, JLY-1225, JLY-124, JLY-155, JLY-215 or JLY-115, all of which are purchased from Jinxi Chemical Research Institute Co., Ltd. The other steps are the same as those of specific embodiments one to seven.
[0037] Specific embodiment 9: This embodiment is a method for preparing a low-hygroscopic medium-temperature curing one-component epoxy adhesive suitable for bonding special-shaped structural composite materials, which is specifically completed in the following steps:
[0038] 1. Weighing materials:
[0039] Weigh 70 to 90 parts of bisphenol A epoxy resin, 10 to 30 parts of multifunctional epoxy resin, 10 to 30 parts of core-shell toughened epoxy resin, 10 to 20 parts of polysulfide rubber modified resin, 8 to 12 parts of dicyandiamide, 1 to 2 parts of 2-ethyl-4-methylimidazole and 7 to 9 parts of fumed silica by weight;
[0040] 2. Mixing:
[0041] 70 to 90 parts of bisphenol A epoxy resin, 10 to 30 parts of multifunctional epoxy resin, 10 to 30 parts of core-shell toughened epoxy resin, 10 to 20 parts of polysulfide rubber modified resin, 8 to 12 parts of dicyandiamide, 1 to 2 parts of 2-ethyl-4-methylimidazole and 7 to 9 parts of fumed silica weighed in step 1 are added to a reactor, stirred and mixed to obtain a mixture;
[0042] 3. Grinding:
[0043] Grinding the mixture obtained in step 2 using a three-roll mill to obtain a single-component paste adhesive;
[0044] 4. Degassing:
[0045] The one-component paste adhesive obtained in step 3 is mixed for a period of time using a planetary mixer to obtain a low-hygroscopic medium-temperature curing one-component epoxy adhesive suitable for bonding special-shaped structural composite materials.
[0046] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the vacuum degree of the planetary mixer in step 4 is less than -0.08MPa, the stirring speed is 500RPM±50RPM, and the mixing time is 60min±10min. The other steps are the same as those of specific embodiments 1 to 9.
[0047] The following examples are used to verify the beneficial effects of the present invention:
[0048] Example 1: A method for preparing a low-hygroscopic medium-temperature curing one-component epoxy adhesive suitable for bonding special-shaped structural composite materials, which is specifically completed by the following steps:
[0049] 1. Weighing materials:
[0050] Weigh 80 parts of bisphenol A epoxy resin, 20 parts of multifunctional epoxy resin, 20 parts of core-shell toughened epoxy resin, 10 parts of polysulfide rubber modified resin, 10 parts of dicyandiamide, 1 part of 2-ethyl-4-methylimidazole and 8 parts of fumed silica according to weight;
[0051] 2. Mixing:
[0052] 80 parts of bisphenol A epoxy resin, 20 parts of multifunctional epoxy resin, 20 parts of core-shell toughened epoxy resin, 10 parts of polysulfide rubber modified resin, 10 parts of dicyandiamide, 1 part of 2-ethyl-4-methylimidazole and 8 parts of fumed silica weighed in step 1 are added into a reactor, stirred and mixed to obtain a mixture;
[0053] 3. Grinding:
[0054] Grinding the mixture obtained in step 2 using a three-roll mill to obtain a single-component paste adhesive;
[0055] 4. Degassing:
[0056] The one-component paste adhesive obtained in step 3 is mixed with a planetary mixer for a period of time to obtain a low-hygroscopic medium-temperature curing one-component epoxy adhesive suitable for bonding special-shaped structural composite materials;
[0057] The vacuum degree of the planetary mixer described in step 4 is -0.09 MPa, the stirring speed is 500 RPM, and the mixing time is 60 min;
[0058] The bisphenol A epoxy resin described in step 1 is E51;
[0059] The multifunctional epoxy resin described in step 1 is triglycidyl p-aminophenol;
[0060] The core-shell toughened epoxy resin described in step 1 is MX-125, purchased from Kanebuchi Corporation of Japan;
[0061] The fumed silica described in step 1 is Cabot TS-530;
[0062] The preparation method of the polysulfide rubber modified resin described in step 1 is specifically completed according to the following steps:
[0063] Add 100 g of low-viscosity epoxy resin and 50 g of liquid polysulfide rubber into a reactor, heat the mixture from room temperature to 120° C. at a heating rate of 2° C. / min under a stirring speed of 400 r / min, and stir continuously at 120° C. for 5 h to obtain a polysulfide rubber modified resin;
[0064] The low viscosity epoxy resin is 1,2-cyclohexanediol diglycidyl ether;
[0065] The liquid polysulfide rubber is JLY-121, which was purchased from Jinxi Chemical Research Institute Co., Ltd.
[0066] Comparative Example 1: The difference between this example and Example 1 is that 10 parts of polysulfide rubber modified resin are omitted. Other steps and parameters are the same as those in Example 1.
[0067] Water absorption test method:
[0068] The adhesive prepared by adding polysulfide rubber modified resin in Example 1 and the adhesive prepared by not adding polysulfide rubber modified resin in Comparative Example 1 were cured at 120° C. for 90 min to obtain two cured samples; the initial weight m1 of the two cured samples was weighed first, and then the two cured samples were immersed in boiling water for 1 d to 7 d, and then the weight m2 after the boiling water immersion time was weighed, and the water absorption rate = [(m2-m1) / m1]×100, and the water absorption rate is shown in Figure 1 As shown;
[0069] Figure 1 The graph is a water absorption rate diagram of the adhesive prepared by adding polysulfide rubber modified resin in Example 1 and the adhesive prepared by not adding polysulfide rubber modified resin in Comparative Example 1 after being immersed in boiling water;
[0070] from Figure 1 It can be seen that the water absorption rate of the adhesive prepared by adding polysulfide rubber modified resin after soaking in boiling water is significantly lower than that of the adhesive prepared without adding polysulfide rubber modified resin, indicating that the moisture and heat resistance of the adhesive is improved after adding polysulfide rubber modified resin.
[0071] Figure 2The initial DMA graphs are of the adhesive prepared by adding polysulfide rubber modified resin in Example 1 and the adhesive prepared by not adding polysulfide rubber modified resin in Comparative Example 1;
[0072] from Figure 2 It can be seen that the glass transition temperature of the adhesive prepared by adding polysulfide rubber modified resin is slightly lower than that of the adhesive prepared without adding polysulfide rubber modified resin, indicating that the heat resistance of the adhesive is slightly reduced after adding polysulfide rubber modified resin.
[0073] Figure 3 DMA graphs of the adhesive prepared by adding polysulfide rubber modified resin in Example 1 and the adhesive prepared by not adding polysulfide rubber modified resin in Comparative Example 1 after being immersed in boiling water for 7 days.
[0074] from Figure 3 It can be seen that the glass transition temperature of the adhesive prepared by adding polysulfide rubber modified resin after being immersed in boiling water for 7 days is higher than that of the adhesive prepared without adding polysulfide rubber modified resin, indicating that the moisture and heat resistance of the adhesive is improved after adding polysulfide rubber modified resin.
[0075] The properties of the adhesive prepared by adding polysulfide rubber modified resin in Example 1 and the adhesive prepared by not adding polysulfide rubber modified resin in Comparative Example 1 are shown in Table 1;
[0076] Table 1 Comparison of adhesive properties before and after adding polysulfide rubber modified resin
[0077]
[0078]
[0079] In Table 1, sequence number 1 is Figure 2 The peak value of the middle curve is obtained, and the sequence number 2 is obtained by Figure 3 The peak value of the middle curve is obtained.
[0080] The bonded materials in No. 3 and No. 4 in Table 1 are carbon fiber / bismaleimide composite materials. The specific method is: apply the adhesive to the bonded surface, and then immediately perform overlapping bonding and curing. The curing conditions are 120°C / 90min, and then perform testing according to GB / T 7124-2008 standard.
[0081] The bonded materials in No. 5 and No. 6 in Table 1 are carbon fiber / bismaleimide composite materials. The specific method is: first apply the adhesive to the bonded surface, then expose it to a humidity environment of 25°C and 60% RH for 24 hours, and then perform overlapping bonding and curing. The curing conditions are 120°C / 90min, and then perform testing in accordance with GB / T 7124-2008 standard.
[0082] The bonded materials in No. 7 and No. 8 in Table 1 are carbon fiber / bismaleimide composite materials. The specific method is: apply the adhesive to the bonded surface, and then immediately perform the stacking bonding and curing, and the curing condition is 120℃ / 90min. Then, the obtained sample is immersed in boiling water for 7 days, and then tested according to GB / T 7124-2008 standard.
Claims
1. A low hygroscopic medium temperature curing one-component epoxy adhesive suitable for bonding special-shaped structural composite materials, characterized in that The epoxy adhesive is prepared by weight from 70 to 90 parts of bisphenol A epoxy resin, 10 to 30 parts of multifunctional epoxy resin, 10 to 30 parts of core-shell toughened epoxy resin, 10 to 20 parts of polysulfide rubber modified resin, 8 to 12 parts of dicyandiamide, 1 to 2 parts of 2-ethyl-4-methylimidazole and 7 to 9 parts of fumed silica.
2. A low hygroscopic medium temperature curing one-component epoxy adhesive suitable for bonding special-shaped structural composite materials according to claim 1, characterized in that The bisphenol A type epoxy resin is E51 or E54.
3. The low hygroscopicity medium temperature curing one-component epoxy adhesive suitable for bonding special-shaped structural composite materials according to claim 1, characterized in that The multifunctional epoxy resin is triglycidyl p-aminophenol or triglycidyl m-aminophenol.
4. The low hygroscopicity medium temperature curing one-component epoxy adhesive suitable for bonding special-shaped structural composite materials according to claim 1, characterized in that The core-shell toughened epoxy resin is MX-125, MX-153, MX-154 or MX-257, MX-125, MX-153, MX-154 or MX-257.
5. The low hygroscopicity medium temperature curing one-component epoxy adhesive suitable for bonding special-shaped structural composite materials according to claim 1, characterized in that The fumed silica is TS-530, TS-610 or TS-720.
6. The low hygroscopicity medium temperature curing one-component epoxy adhesive suitable for bonding special-shaped structural composite materials according to claim 1, characterized in that The preparation method of the polysulfide rubber modified resin is specifically completed according to the following steps: Add 100 g of low-viscosity epoxy resin and 10 g to 100 g of liquid polysulfide rubber into a reactor, heat the mixture from room temperature to 120°C to 130°C at a heating rate of 1°C / min to 5°C / min under a stirring speed of 300 r / min to 500 r / min, and stir continuously at 120°C to 130°C for 4 h to 5 h to obtain a polysulfide rubber modified resin.
7. The low hygroscopicity medium temperature curing one-component epoxy adhesive suitable for bonding special-shaped structural composite materials according to claim 6, characterized in that The low-viscosity epoxy resin is 1,2-cyclohexanediol diglycidyl ether or 1,4-cyclohexanedimethanol diglycidyl ether.
8. The low hygroscopicity medium temperature curing one-component epoxy adhesive suitable for bonding special-shaped structural composite materials according to claim 6, characterized in that The liquid polysulfide rubber is JLY-121, JLY-1225, JLY-124, JLY-155, JLY-215 or JLY-115.
9. The method for preparing a low hygroscopic medium temperature curing one-component epoxy adhesive suitable for bonding special-shaped structural composite materials as claimed in claim 1, characterized in that The preparation method is specifically completed according to the following steps:
1. Weighing materials: Weigh 70 to 90 parts of bisphenol A epoxy resin, 10 to 30 parts of multifunctional epoxy resin, 10 to 30 parts of core-shell toughened epoxy resin, 10 to 20 parts of polysulfide rubber modified resin, 8 to 12 parts of dicyandiamide, 1 to 2 parts of 2-ethyl-4-methylimidazole and 7 to 9 parts of fumed silica by weight; 2. Mixing: 70 to 90 parts of bisphenol A epoxy resin, 10 to 30 parts of multifunctional epoxy resin, 10 to 30 parts of core-shell toughened epoxy resin, 10 to 20 parts of polysulfide rubber modified resin, 8 to 12 parts of dicyandiamide, 1 to 2 parts of 2-ethyl-4-methylimidazole and 7 to 9 parts of fumed silica weighed in step 1 are added to a reactor, stirred and mixed to obtain a mixture; 3. Grinding: Grinding the mixture obtained in step 2 using a three-roll mill to obtain a single-component paste adhesive; 4. Degassing: The one-component paste adhesive obtained in step 3 is mixed for a period of time using a planetary mixer to obtain a low-hygroscopic medium-temperature curing one-component epoxy adhesive suitable for bonding special-shaped structural composite materials.
10. The method for preparing a low hygroscopicity medium temperature curing one-component epoxy adhesive suitable for bonding special-shaped structural composite materials according to claim 9, characterized in that The vacuum degree of the planetary mixer described in step 4 is less than -0.08MPa, the stirring speed is 500RPM±50RPM, and the mixing time is 60min±10min.
Citation Information
Patent Citations
Two-component toughened anti-shock epoxy structural adhesive and preparation method thereof
CN104497941A
High and low temperature resistant single-component epoxy structural adhesive as well as preparation method and application thereof
CN115772373A
Cited By
Nano indium-iron microcrystalline adhesive and curing process
CN120442199A
Carbon fiber connecting glue and curing process
CN122648042A